Herpes zoster in inflammatory bowel disease: pathogenesis, therapy-related risks, and prevention strategies - Guiqin Wu; Ting Xiang; Wenxin Wang; Qing Zhou (The Egyptian Journal of Internal Medicine, 2026)
Abstract Inflammatory bowel disease (IBD) is a chronic, immune-mediated condition characterized by inherent immune dysregulation, which is further compounded by immunosuppressive therapies. Patients with IBD face a 1.5- to 1.7-fold elevated risk of herpes zoster (HZ), often at a younger age, with immunosuppression as the primary driver. Beyond increasing clinical burden, HZ leads to debilitating complications such as postherpetic neuralgia, profoundly diminishing quality of life. While anti-tumor necrosis factor (TNF) and Janus kinase (JAK) inhibitors are effective in controlling IBD inflammation, they concurrently elevate HZ risk—with JAK inhibitors exhibiting a dose-dependent effect via disruption of interferon signaling. Despite the availability of the recombinant zoster vaccine (RZV), which demonstrates robust immunogenicity and a favorable safety profile even in immunocompromised patients, vaccination uptake remains suboptimal. This narrative review examines the epidemiological characteristics, immunological pathogenesis, and therapy-specific risk factors of HZ in IBD. We analyze the differential impact of immunosuppressive therapies, evaluate RZV immunogenicity and safety, and synthesize current preventive strategies. Our aim is to provide a practical clinical framework to guide prevention and management of HZ in patients with IBD.